2018
DOI: 10.3389/fmicb.2018.01924
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Edged Character of Quorum Sensing Signaling Molecules in Microbial Extracellular Electron Transfer

Abstract: Quorum sensing (QS) is a central mechanism for regulating bacterial social networks in biofilm via the production of diffusible signal molecules (autoinducers). In this work, we assess the contribution of QS autoinducers to microbial extracellular electron transfer (EET) by Pseudomonas aeruginosa strain PAO1 and three mutants pure culture-inoculated in microbial electrolysis cells (MECs) and microbial fuel cells (MFCs). MECs inoculated with different P. aeruginosa strains showed a difference in current generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Unlike bacteria coupling anaerobic respiration with high EET capability 7,12,44 , the extent of EET in the fermentative microbes is often low, wherein the number of electrons is less than 1% of the total metabolic electron flux. However, the low extent of EET facilitates their growth and changes fermentation product and effciciency 39,43,45,46 . Here, we have shown that a low level of EET in a fermentative microbe (S. mutans UA 159) modified the fermentation balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike bacteria coupling anaerobic respiration with high EET capability 7,12,44 , the extent of EET in the fermentative microbes is often low, wherein the number of electrons is less than 1% of the total metabolic electron flux. However, the low extent of EET facilitates their growth and changes fermentation product and effciciency 39,43,45,46 . Here, we have shown that a low level of EET in a fermentative microbe (S. mutans UA 159) modified the fermentation balance.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the metabolic shift under OCV and SA conditions occurred with a small amount of flavin reduction. Therefore, the Rex may be activated and support the colonization, biofilm formation, and syntropy among these pathogens via redox-active substrates such as secondary metabolites abundant in biofilm 50 , in addition to concentration-dependent mechanisms such as quorum sensing 46 . Rex regulated fermentative metabolism in the EET-capable gut pathogen Listeria monocytogenes was found to be critical for the production of virulence factors required for survival and invasion of the Gastrointestinal tract 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the EET efficiency of Mtr-expressing E. coli is of particular interest for biosensing because it can increase the signal-to-noise ratio, enabling higher sensitivity detection. In recent years, much progress has been made in engineering the electrical communication between bacteria and electrodes, such as responding to specific chemicals using chemical-sensitive promoters (Golitsch et al, 2013; Webster et al, 2014; Yang et al, 2018), miniaturized reactors with optimized structure design (Zhou et al, 2017), and modified material-bacteria interface (Zajdel et al, 2018). Enhancing the bioelectrical performance of Mtr-expression E. coli offers a reliable chassis in biosensing applications.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the removal efficiency of nitrite can be accredited to the increase in biomass through the early activated QS mechanism due to the dosage of 3-oxo-C12-homoserine lactone [ 108 ]. In a demonstration by Yang, Zhou [ 109 ], it was also observed that QS autoinducers contributed to microbial extracellular electron transfer by P. aeruginosa PAO1. In this investigation, three MECs were inoculated with three different mutant cultures of P. aeruginosa , individually, which showed an increase in the current generation in all the MECs due to the overproduction of PQS.…”
Section: Application Of Bacterial Signalling Mechanisms In Metsmentioning
confidence: 99%